Effects of water nanodroplets on skin moisture and viscoelasticity during air‐conditioning. Issue 4 (17th April 2013) - Ohno, Hideo; Nishimura, Naoki; Yamada, Kuniyuki; Shimizu, Yuuki; Iwase, Satoshi; Sugenoya, Junichi; Sato, Motohiko
<x xml:space="preserve">Abstract</x> Background/purpose In air‐conditioned rooms, dry air exacerbates some skin diseases, for example, senile xerosis, atopic dermatitis, and surface roughness. Humidifiers are used to improve air dryness, which often induces excess humidity and thermal discomfort. To address this issue, we investigated the effects of water nanodroplets (mist) on skin hydration, which may increase skin hydration by penetrating into the interstitial spaces between corneocytes of the stratum corneum (SC) without increasing air humidity. Methods We examined biophysical parameters, including skin conductance and transepidermal water loss (TEWL), and biomechanical parameters of skin distension/retraction before and after suction at the forehead, lateral canthus, and cheek, with or without mist, in a testing environment (24°C, 35% relative humidity) for 120 min. Results In the group without mist, TEWL values significantly decreased at all the sites after 1 h compared with the initial values. However, in the presence of mist, TEWL values were maintained at the initial values through the test, yielding significant differences vs. the group without mist. There were no significant differences between mist and mist‐free groups in terms of skin conductance. Skin distension was significantly increased in the group with mist compared with that in the group without mist at the forehead and cheek, suggesting a softening effect of mist. Conclusion Skin deformation of the face was improved by mist, suggesting hydration of the SC by mist. The change in TEWL was influenced by mist, suggesting supply of water to the skin, particularly the SC, by mist. These data indicated that a mist of water nanodroplets played an important role in softening skin in an air‐conditioned room without increasing excess humidity.